Implementasi Distribution Requirement Planing dan Saving Matrix untuk Meminimasi Biaya Distribusi PT Garuda Food Gorontalo - Raman S. Mau; Jamal Darusalam Giu; Trifandi Lasalewo (Jurnal Ilmu Teknik Terapan, 2026)
The development of the industrial world is experiencing intense competition in the current industrial era, both those engaged in the production and distribution of goods. For this reason, good distribution planning can ensure the availability of products needed by consumers. Without distribution, producers will find it difficult to market their products, and consumers will find it difficult to find the products they need. The research aims to plan distribution properly and efficiently. In this case, Distribution Requirement Planning plays a pivotal role for both integrated manufacturing distribution system and pure distribution system with the need for time phasing supply at each level of the distribution network. This research is classified as descriptive research or research whose main characteristics are providing objective explanation, comparison, and evaluation as material for making decision for authorities. The aim of descriptive research is to find an explanation for a fact or event that occurs, for example, condition or relationship that exists, opinion that develops, consequence or effect that occurs, or ongoing trend